Relationship between the area of isopters and Vigabatrin dosage during two years of observation - Nowomiejska, Katarzyna; Jedrych, Marian; Brzozowska, Agnieszka; Rejdak, Konrad; Zarnowski, Tomasz; Koss, Michael Janusz; Ksiazek, Katarzyna; Ksiazek, Piotr; Maciejewski, Ryszard; Juenemann, Anselm G.; Schiefer, Ulrich; Rejdak, Robert (BMC ophthalmology, 2014)
The aim of the study was to evaluate the relationship between the area of isopters obtained using semi-automated kinetic perimetry (SKP) and Vigabatrin dosage in epilepsy patients with pretreatment baseline examination during 2-years of the follow-up.